A preliminary assessment of a new dedicated endodontic software for use with CBCT images to evaluate the canal complexity of mandibular molars. (18th September 2017) - Gambarini, G.; Ropini, P.; Piasecki, L.; Costantini, R.; Carneiro, E.; Testarelli, L.; Dummer, P. M. H.
Abstract: Aim: To investigate in vivo the complexity of canals within mesial roots of mandibular molars using 3D Endo™ software linked to CBCT images. Methodology: The CBCT images of 100 mandibular first molars were analysed using the 3D Endo™ software. The number of canals in the mesial roots, the presence of apical confluences, the canal lengths and the canal configurations using Vertucci's classification were evaluated in buccolingual (BL) and mesiodistal (MD) views. The software allowed the visualization of canal trajectories in three dimensions using a coloured outline, which was used to develop a new objective scoring system to provide an overall assessment of canal complexity. Data were analysed statistically usinganova and t ‐tests with the significance set at P  <   0.05. Results: Vertucci type IV canals were found in 44% of the cases, whilst 54% were type II. The mean distance from the apical foramen to the orifice was 13.15 mm (±1.21) and that between a confluence and the foramen, 2.81 mm (±1.13). The number of curvatures and the canal complexity scores in the MD view were significantly higher than in the BL view ( P  <   0.05). The scores were not directly correlated to the canal (MB versus ML), to the canal length or to the presence of confluences. Conclusions: 3D Endo software features the automatic detection and measurement of several anatomical canal parameters, and is a promising tool for the study of canal complexity in vivo . The unpredictable anatomy of the mesial roots of mandibular molars highlights the value of a three‐dimensional preoperative evaluation of each case. The proposed scoring system aims to provide the clinician with an overall assessment of canal complexity.